When did the future Antiochos iv arrive in Athens? - Scolnic, B. (Hesperia, 2014)
The mention of an Antiochos in an Athenian inscription, I 7453, which dates to 178/7 b.c., has led scholars to accept that the future Antiochos IV lived in Athens from 178 to 175, and was not just present in the city in 175, as a statement by Appian seems to indicate. A reevaluation of the evidence calls into question both this extended sojourn and the identification of the Antiochos in the inscription, inviting us to reconsider the circumstances and the chronology of events surrounding the accession of Antiochos IV. © The American School of Classical Studies at Athens.
1 citations (Crossref) [2023-10-31]
Keywords: dept.jst

Is Daniel 11:1-19 based on a ptolemaic narrative? - Scolnic, Benjamin (Journal for The Study of Judaism, 2014)
Daniel 11 is considered an exceptional Biblical text because of its interest in and accuracy about historical and political events in the Hellenistic world. A recent theory suggests that the author was a former Seleucid scribe; another theory posits the use of a Ptolemaic propaganda document. The approach here will be inductive, reading out from the text to adduce evidence that the author of Daniel 11 either used or reflected the attitudes of Ptolemaic narrative, not necessarily because he was pro-Ptolemaic but because it suited his anti-Antiochene purpose. © Koninklijke Brill NV, Leiden, The Netherlands.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/035-586-778-649-478 tex.type: [object Object]
Keywords: Bible; Daniel; Maccabean; Source criticism; dept.jst